2019
DOI: 10.4314/ahs.v19i2.28
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles inhibits quorum sensing and virulence in Pseudomonas aeruginosa

Abstract: BackgroundQuorum sensing inhibitionis an advanced strategy that aims to interfere with bacterial cell-to-cell communication systems (quorum sensing), which regulate virulence factors production in Pseudomonas aeruginosa, in order to overcome the globalcrisis of antimicrobial resistance.ObjectivesStudy the potential quorum sensing inhibitory effect of Zinc oxide (ZnO)nanoparticlesin Pseudomonas aeruginosa and the impact on production of virulence factors.MethodsQuorum sensing inhibitory effect of ZnO was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 27 publications
4
13
0
Order By: Relevance
“…In accordance with our data, Saleh et al reported that ZnO-np had a signi cant decrease in the relative expression of QS-genes lasI, lasR, rhlI, rhlR, pqsA and pqsR. Additionally, ZnO signi cantly decreased the pathogenesis of P.aeruginosa in vivo [12].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our data, Saleh et al reported that ZnO-np had a signi cant decrease in the relative expression of QS-genes lasI, lasR, rhlI, rhlR, pqsA and pqsR. Additionally, ZnO signi cantly decreased the pathogenesis of P.aeruginosa in vivo [12].…”
Section: Discussionsupporting
confidence: 92%
“…Researchers showed that ZnO NPs were able to inhibit QS in P. aeruginosa by down regulating lasR. lasI, rhl I, and rhl R (Saleh et al, 2019). Another study showed that ZnO NPs were able to reduce the swimming and swarming motility within P. aeruginosa and also showed its efficacy against the pqs and las system of QS (Khan et al, 2020).…”
Section: Inhibition Of Quorum Sensing By Micro Biogenic Zno Npsmentioning
confidence: 99%
“…Real-time rt-PCR reaction was prepared with a final volume of 20 µl (master mix: 10 µl, Forward primer: 0.8 µl, Reverse primer: 0.8 µl, Reverse transcriptase: 0.2 µl, RNase inhibitor, 0.4 µl, Water up to 16 µl and Template: 4 µl). Different genes and primers were listed in Table 1 [11][12][13][14]. Four negative control samples containing deionized water instead of template, one for each gene were included in the same PCR run.…”
Section: Rt-pcrmentioning
confidence: 99%